ANALISIS PENINGKATAN KUALITAS PRODUK BATIK MENGGUNAKAN PENDEKATAN QUALITY FUNCTION DEPLOYMENT (QFD) (Studi Kasus Batik BL Di Pekalongan) - Adieba, Muhammad Haris; Dwiyanto, Bambang Munas (Faculty of Economics and Business Diponegoro University, 2016)
The competition in the batik world has rapid development nowadays. It can be seen from how many batik products in every city or even country with various qualities. This study aims to improve the product quality of Batik BL Pekalongan in terms of facing competition. The dependent variable is the product quality and the independent variable is the interest rate quality perception and level of satisfaction. The samples are 35 resellers from Batik BL Pekalongan. The data used were obtained through questionnaires and interviews. Data were analyzed using descriptive analysis. Based on the HOQ, QFD analysis was made to improve the quality. The findings of the research are: 1) the value of customer satisfaction is still minus, meaning that customers are not satisfied yet with the product of batik BL Pekalongan ; 2) the highest degree of difficulty encountered is reliable employees. The main priority is based on the results of the targets prioritization, which should be the concern of the technical descriptor, while product developing must prioritize its competitive advantages, batik products style and product performance. The main priority of the hows, the thing that need consideration the most in developing the product designs are more competitive prices and products consistency.